Understanding ‘sin’ in the Johannine epistles - Merwe, Dirk G. van der (Verbum et Ecclesia, 2005)
The author of the Johannine Epistles has a good deal to say about sin. He abhors sin, seeing it as incompatible with God’ s character (oJ qeo;" fw`" ejstin, 1:5; [oJ qeo;"] divkaiov" ejstin, 2:29; and oJ qeo;" ajgavph ejstivn, 4:8) and with the status of believers as God’ s children. In this article attention is given to the following relevant aspects for understanding ‘hamartiology’ in the Johannine epistles from a ‘family perspective’: (1) the ‘family of God’ metaphor is used as the setting in which the author describes his symbolic narrative; (2) a differentiation is made between sin inside and sin outside the family; (3) sin outside the family is also described in terms of reciprocals to emphasize its condemnation; (4) finally, he focuses on the ‘forgiveness of sin’. This investigation is done against the socio-religious circumstances of the Johannine community in order to understand the Elder’ s ethical and doctrinal definitions of sin.
free